Faktor-faktor yang Mempengaruhi Angka Putus Sekolah di Desa Mappesangka Kecamatan Ponre Kabupaten Bone - Sarah Damayanti; Uca Sideng; Sukri Nyompa (UNM Geographic Journal, 2020)
This study aimed to determine what factors that influence school dropouts in Mappesangka Village, Ponre District, Bone Regency. The targets of this study were 27 school dropouts, parents of school dropouts and the government of Mappesangka Village, Ponre District, Bone Regency. This is a descriptive qualitative research with survey method. Data collection techniques used were observation, interviews, and documentation. The method of determining the sample was by using saturated sampling technique in which there were 27 school dropouts and all of them were included in the population. The results of the study showed that the lack of interest in learning and attending school among children who dropped out of school was the main cause with 17 children or 65%, the social environment also greatly affected the cessation of children attending school which obtained 15 children or 57%. In addition, it was also caused by the low level of parents' economy which obtained 8 children or 29,62%.